Applied mathematics - Tan, S.T. (Thomson Brooks/Cole, 2007)
In the market-leading APPLIED MATHEMATICS FOR THE MANAGERIAL, LIFE, AND SOCIAL SCIENCES, Soo T. Tan provides an accurate, accessible presentation of finite mathematics and applied calculus combined with just the right balance of applications, pedagogy, and technology to help students succeed in the course. The new Fourth Edition includes highly interesting current applications and Microsoft Excel exercises to help stimulate student motivation. An exciting new array of supplements, including iLrn" Mathematics and the Interactive Video Skillbuilder CD-ROM, provides students with extensive learning support so instructors will have more time to focus on teaching the core concepts